Strategic Management Approaches to Healthcare System Resilience: A Systematic Review Post-Pandemic Era - Hadija Hadija; Harmayanto Harmayanto; Rina Octavia (Lembaga Pengembangan Kinerja Dosen, 2026)
The COVID-19 pandemic exposed profound vulnerabilities within global healthcare systems, catalyzing an urgent need for strategic management frameworks capable of sustaining resilience under extraordinary pressure. This systematic review examines strategic management approaches adopted by healthcare organizations during and after the COVID-19 pandemic to build and sustain system resilience. Following PRISMA guidelines, a comprehensive search of PubMed, Scopus, Web of Science, and CINAHL databases was conducted, yielding 42 peer-reviewed articles published between 2020 and 2024. Findings reveal four dominant strategic clusters: (1) adaptive governance and decentralized decision-making, (2) digital transformation and health information systems integration, (3) supply chain resilience and resource optimization, and (4) workforce capacity building and psychological safety. Evidence indicates that healthcare organizations employing proactive, integrated strategic frameworks demonstrated significantly greater resilience outcomes compared to those relying on reactive operational adjustments. This review contributes theoretical and practical insights for policymakers and health system administrators navigating the post-pandemic landscape, emphasizing the necessity of embedding resilience as a core organizational competency.